Multiple dose of liquid antacid enhance simvastatin bioavailability in Malaysian male volunteers - Akhali, Khaled M Al; Alavudeen, Sirajudeen S (Asian Journal of Pharmaceutics (AJP), 2014)
The effect of a liquid antacid on the oral bioavailability of simvastatin 40 mg tablet was evaluated in 9 healthy Malaysian male volunteers in a randomized, single dose, two‑way crossover study. The drug was administered following an overnight fast or a liquid antacid. The plasma concentration of simvastatin was determined by using a validated HPLC-MS-MS method. An effect of liquid antacid on the bioavailability was indicated 95% increase in the AUC of simvastatin with antacid state comparing to fasting state. The study was concluded that liquid antacid had effect on the increasing pH of gastrointestinal tract which leads to increasing the lactone form of simvastatin stability and improve the dissolution of the drug by increasing gastric residence time. This study revealed that simvastatin is pH‑dependent. Key words: Liquid antacid, fasting, simvastatin bioavailability